Picoplankton structure in clear and turbid eutrophic shallow lakes: A seasonal study - Silvoso, Julieta (2011)
The relative abundance of the different picoplankton components (eukaryotic picophytoplankton (Peuk), picocyanobacteria (Pcy) and bacterioplankton), and their relationships with the lake conditions were studied in three types of shallow lakes from the Pampa Plain (Argentina) that differ in their optical properties: clear-vegetated, phytoplankton-turbid and inorganic-turbid. All the selected lakes, but one, are characterized by their different alternative steady state (clear-vegetated and phytoplankton-turbid water phases) following the model proposed by Scheffer et al. (1993).Autotrophic and heterotrophic picoplankton abundances were analyzed seasonally in relation to environmental variables. All the lakes presented high concentrations of total nitrogen (TN) (>229μgL-1), total phosphorus (TP) (>46μgL-1) and dissolved organic carbon (DOC) (>13.7mgL-1). Clear-vegetated lakes were characterized by vertical diffuse PAR (photosynthetic active radiation) attenuation coefficient (kdPAR) lower than 11m-1, whereas inorganic-turbid lake always showed values higher than 21.1m-1. The euphotic zone depth (Z1%) was wider in clear-vegetated lakes (40-140cm) and thinner in the inorganic-turbid (10-20cm). The phytoplankton-turbid lakes presented a wide range in the values of these variables (kdPAR: 5.2-35.8m-1; Z1%: 10-90cm). Phytoplankton chlorophyll-a (Chl-a) strongly differed, ranging from 1.6 to 334.6μgL-1. Picophytoplankton was mainly represented by phycocianine-rich (PC-rich) Pcy in all cases, dominating over Peuk algae. The total and relative abundances of eukaryotic picophytoplankton, Pcy and bacterioplankton, as well as the size structure of the phytoplankton community differed among the water bodies. In general, clear-vegetated water bodies exhibited similar abiotic characteristics, picophytoplankton/bacterioplankton ratios, and phytoplankton size structure. Contrarily, no clear trend was identified for the group of turbid lakes. The contrasting results obtained for the importance of the picoplankton components in phytoplankton-turbid shallow lakes evidence that the availability of the energetical and nutrient resources cannot be solely considered to predict their relative importance in this type of shallow lake.